Solvable nonlinear evolution PDEs in multidimensional space - Calogero, F.; Sommacal, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
A class of solvable (systems of) nonlinear evolution PDEs in multidimensional space is discussed. We focus on a rotation-invariant system of PDEs of Schrödinger type and on a relativistically-invariant system of PDEs of Klein-Gordon type. Isochronous variants of these evolution PDEs are also considered.